Lectures on Polish value theory - Porebski, Czeslaw. (Studien zur Österreichischen Philosophie, 2019)
This book offers a synoptic introduction to an important chapter of Polish 20th century philosophy, by introducing the studies of Kazimierz Twardowski, Tadeusz Czeżowski, Tadeusz Kotarbiński, Władysław Tatarkiewicz, Roman Ingarden, Henryk Elzenberg, Maria Ossowska, and Józef Maria Bocheński and how they contributed to value theory, ethics and aesthetics. These philosophers differed in their more definite interests, methodological approaches, and main results and yet their investigations share a number of characteristic features. Questions of value, considered as extremely vital, are treated with care and precision. In spite of the richness of their insights and an impressive number of detailed results these philosophers refrain from hasty conclusions, trying here, as elsewhere, to conduct their studies in an intellectually and morally responsible way.